Merchant guilds in ancient Mesoamerica and their origins - Paris, Elizabeth H. (Frontiers in Human Dynamics, 2025)
Historical records and material culture of professional merchant organizations, including merchant guilds, provide important insights into their activities, hierarchies, and signifiers of membership. As historical examples indicate, signifiers of membership are common in cross-cultural examples of merchant guilds, and frequently include emblems inscribed on jewelry and personal objects. These guilds frequently worshiped supernatural patrons, which were commonly inscribed on membership signifiers such as rings, tokens, or cards. This article argues that the pochteca of the Aztec imperial era meets the historical definition of a guild as a self-organized, membership-based group, and reflects many of the same organizing principles observed for Medieval/Renaissance guilds in Europe. Many of the characteristics of the pochteca can also be used to identify earlier merchant organizations where written records are scarce or lacking. This article argues that copper anthropomorphic face rings depicting merchant deities emerged as signifiers for professional merchants among the Late Classic and Early Postclassic Maya of eastern Chiapas and Guatemala, many of whom held elite status, and were subsequently popularized among professional merchants in many other areas of Mesoamerica by the Late Postclassic period.